2021
DOI: 10.3390/app112210744
|View full text |Cite
|
Sign up to set email alerts
|

Zoning Control Technology of Gob-Side Roadway Driving with Small Coal Pillar Facing Mining in a Special Isolated Island Working Face: A Case Study

Abstract: The gob-side roadway in an isolated island working face is a typical representative of a strong mining roadway, which seriously restricts the efficient and safe production of underground coal mines. With the engineering background of the main transportation roadway 1513 (MTR 1513) of the Xinyi Coal Mine, this paper introduces the engineering case of gob-side roadway driving with small coal-pillar facing mining in an isolated island working face under the alternate mining of wide and narrow working faces. Throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…With the increasing demands of coal resources and the construction of resource-saving coal mines, the implementation of narrow coal pillars to arrange working faces has become a more popular choice of more mines [1][2][3]. However, large deformation and damage of the GSR has also become a large problem, plaguing safe production in mines, especially for close extra-thick coal seams.…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing demands of coal resources and the construction of resource-saving coal mines, the implementation of narrow coal pillars to arrange working faces has become a more popular choice of more mines [1][2][3]. However, large deformation and damage of the GSR has also become a large problem, plaguing safe production in mines, especially for close extra-thick coal seams.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [18] found that when the roadway was located within the fracture line of the main roof, the deformation was mainly affected by the roof rotation, and when it was located outside the fracture line, the deformation was mainly affected by lateral stress. Han et al [19] believed that the deformation characteristics of the gob-side roadway are divided into the heading face mining zone, the mining influenced zone, and the mining stability zone.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang [23] presented an approach for evaluating, designing, and optimizing EDG and yield pillar based on the results of numerical simulations and field practice. Han et al [24][25][26] considered special geological situations to drive an entry along the gob, such as in an isolated island working face, in a deep soft-broken coal seam, or in a working face adopting roadway side sealing technology. The targeted control techniques of the surrounding rock were proposed and successfully applied in the field practices.…”
Section: Introductionmentioning
confidence: 99%